2009
DOI: 10.1287/opre.1080.0637
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Bidding in Combinatorial Auctions

Abstract: In a combinational auction in which bidders can bid on any combination of goods, bid data can be of exponential size. We describe an innovative new combinatorial auction format in which bidders submit "matrix bids". The advantage of this approach is that it provides bidders a mechanism to compactly express bids on every possible bundle. We describe many different types of preferences that can be modeled using a matrix bid, which is quite flexible, supporting additive, subadditive, and superadditive preferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In Table 3, we give the average computation times Table 1 Average computation times (s) for n bidders and m items using BOI that resulted from solving the assignment based formulation (2)-(6) with the Ilog Cplex 8.1 branch-and-cut algorithm with standard settings (B&C), which is basically the approach followed in Day and Raghavan [13]. Horizontally, the number of bidders n varies from 5 to 100, while the number of items m auctioned ranges from 5 to 50 vertically.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Table 3, we give the average computation times Table 1 Average computation times (s) for n bidders and m items using BOI that resulted from solving the assignment based formulation (2)-(6) with the Ilog Cplex 8.1 branch-and-cut algorithm with standard settings (B&C), which is basically the approach followed in Day and Raghavan [13]. Horizontally, the number of bidders n varies from 5 to 100, while the number of items m auctioned ranges from 5 to 50 vertically.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, from their computational experiments, Day and Raghavan [13] conclude that the computation time for the general combinatorial auction is higher and grows much faster than for the matrix bid auction. Moreover, they manage to solve the winner determination problem for matrix bid auctions with 72 items, 75 bidders and over 10 23 bids, whereas for the general combinatorial auction, the largest instances that can be solved have 16 items, 25 bidders, and less than 10 9 bids.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…recently proposed an iterative combinatorial exchange mechanism that incorporates the TBBL language. Day and Raghavan (2006) introduced a matrix bidding language and showed that it is as expressive as that proposed by Boutilier and Hoos (2001) with the k − of operator. A bidder expresses its preferences through a matrix B in which a column j represents a fictive "unit-demand" agent and a row i corresponds to an auctioned item.…”
Section: Motivation and State Of The Artmentioning
confidence: 99%